Optimization of the fermentation of fireweed (Epilobium angustifolium) shoot - Galambosi, B.; Galambosi, Zs.; Shikov, A. N.; Kosman, V. M.; Pozharitskaya, O. N.; Kauppinen, S.; Makarov, V. G. (Natural Resources Institute Finland, Luke, 2016)
Infusion from fermented Epilobium angustifolium L. leaves (Ivan tsay, Koporye tea) is traditionally consumed in Russia for the treatment of stomach ulceration, gastritis, and sleeping disorders. The traditional production method of Ivan tea includes of several labour-consuming steps. During 2012–2014 in the frame of SPECICROP project a semi-industrial fermentation process of shoots of Epilobium angustifolum L. was studied. The experiments were carried out in MTT Agrifood Research Finland Mikkeli in cooperation with St.-Petersburg Institute of Pharmacy, St-Petersburg, Russia. On the base of these experiments we concluded that there is a possibility to produce Ivan tea commercially from a 40 cm shoot yield instead of leaves. The steps and the optimized parameters of the process are described on the proposed technological recommendation. The production process can be reproduced in the conditions of small-scale enterprises.
Keywords: Epilobium angustifolium; fermentointimenetelmä; tekninen suositus; shoot yield; fermentation parameters; technological recommendation; fermentointi; menetelmät; suositukset